Research on the relationship between perceived social support and positive coping style of fire rescue personnel with the mediating effects of positive emotions and meaning in life - Zhang, Yuhan; Wang, Zeqing; Qin, Yuying; Jin, Song (Scientific reports, 2025)
In the realm of emergency response, the mental health of fire rescue personnel holds significant importance. Given that they are constantly confronted with sudden disasters, the coping style they adopt has a profound impact on their overall well-being. Although it is already known that there exists a connection between perceived social support and positive coping, the underlying mechanisms remain to be explored. This study was designed with the aim of clarifying how perceived social support influences the positive coping style among fire rescue personnel, as well as identifying the mediating roles played by positive emotions and the sense of meaning in life. To this end, we conducted a survey using relevant scales among 354 fire rescue personnel. The results demonstrated positive correlations among relevant factors and revealed that positive emotions and the sense of meaning in life have significant mediating effects. This paper reveals the internal mechanisms underlying the relationship between perceived social support and positive coping style among fire rescue personnel, aiming to contribute to the improvement of the mental health and rescue capabilities of fire rescue personnel by providing a theoretical basis and practical guidance for improving the mental health and rescue ability of fire rescue personnel. Moreover, they may serve as a guide for future intervention strategies and offer valuable insights for similar research in other high-stress occupations, thereby enhancing the overall effectiveness of emergency response efforts.